Outcomes of liver transplantation with thoracoabdominal normothermic regional perfusion: a matched-controlled initial experience in Spain - Secanella, Luis; Alconchel, Felipe; López-Monclús, Javier; Toledo-Martínez, Enrique; Barrios, Oriana; Ramírez, Pablo; Jiménez-Garrido, Manuel Cecilio; Rodríguez-Sanjuán, Juan Carlos; Royo-Villanova, Mario; Moreno-González, Gabriel; Lladó, Laura (Frontiers in Transplantation, 2023)
Thoracoabdominal (TA) normothermic regional perfusion (NRP) should allow the safe recovery of heart and liver grafts simultaneously in the context of controlled donation after circulatory death (cDCD). We present the initial results of cDCD liver transplantation with simultaneous liver and heart procurement in Spain until October 2021. Outcomes were compared with a matched cohort of cDCD with abdominal NRP (A-NRP) from participating institutions. Primary endpoints comprised early allograft dysfunction (EAD) or primary non-function (PNF), and the development of ischemic-type biliary lesions (ITBL). Six transplants were performed using cDCD with TA-NRP during the study period. Donors were significantly younger in the TA-NRP group than in the A-NRP group (median 45.6 years and 62.9 years respectively, p = 0.011), with a median functional warm ischemia time of 12.5 min in the study group and 13 min in the control group. Patient characteristics, procurement times, and surgical baseline characteristics did not differ significantly between groups. No patient in the study group developed EAD or PNF, and over a median follow-up of 9.8 months, none developed ITBL or graft loss. Extending A-NRP to TA-NRP for cardiac procurement may be technically challenging, but it is both feasible and safe, showing comparable postoperative outcomes to A-NRP.